2015
DOI: 10.1016/j.bmcl.2014.12.094
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-derivatized minihepcidins retain biological activity

Abstract: Minihepcidins are small peptides that mimic biological activity of the iron-regulatory hormone hepcidin. Structurally, they contain thiol-free-cysteine residue in position 7 which is crucial for their bioactivity. Nonetheless, free sulfhydryl group is not desirable in pharmaceutical entities as it may lead to dermatological side effects. Moreover free thiol moiety is quite reactive and depending on conditions/reagents may be alkylated and/or oxidized giving various Cys-derivatives: S-alkyl cysteines, sulfoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 24 publications
2
46
0
Order By: Relevance
“…The profound block of iron export through K8R was achieved despite impaired Fpn degradation, as determined by western blotting ( Figure 5B), and despite the lack of degradation or punctate structures characteristic of endocytosis, as shown by microscopy ( Figure 5C). PR73, 41 a minihepcidin that was engineered to bind to Fpn more strongly than hepcidin, was 10 times more potent than hepcidin in inducing ferritin retention without endocytic degradation of K8R Fpn (supplemental Figure 12).…”
Section: Characterization Of K8r Fpn Mutant and Evidence Of Its Occlumentioning
confidence: 99%
“…The profound block of iron export through K8R was achieved despite impaired Fpn degradation, as determined by western blotting ( Figure 5B), and despite the lack of degradation or punctate structures characteristic of endocytosis, as shown by microscopy ( Figure 5C). PR73, 41 a minihepcidin that was engineered to bind to Fpn more strongly than hepcidin, was 10 times more potent than hepcidin in inducing ferritin retention without endocytic degradation of K8R Fpn (supplemental Figure 12).…”
Section: Characterization Of K8r Fpn Mutant and Evidence Of Its Occlumentioning
confidence: 99%
“…They discovered specific hydrophobic/aromatic residues required for hepcidin‐Fpn1 binding and obtained evidence in vitro that a thiol‐disulfide interaction between Fpn1 C326 and the hepcidin disulfide cage may stabilize binding . They showed that S‐vinyl‐derivatization of minihepcidin(s) may be a suitable approach in the development of physiologically active agonists of hepcidin . They also improved the half‐life and potency of these peptides through engineering and demonstrated that treatment with minihepcidins to mice mimics the iron‐restrictive effect of endogenous hepcidin, as reflected by improved anemia, iron overload, ineffective erythropoiesis, the lifespan of circulating red blood cells and splenomegaly, and reduced hemichrome formation and ROS .…”
Section: Hepcidin and The Treatment Of Neurodegenerative Disordersmentioning
confidence: 99%
“…Other hepcidin sequestering agents to be considered as a novel treatment options include mimicking soluble hemojuvelin; suppression of bone morphogenic protein (BMP) receptors as dorsomorphin; disruption IL-6 activation and there the action of tocilizumab, neutralizing antibody to IL-6, that has been already approved for rheumatoid arthritis and has been proved to ameliorate anaemia in Castleman's disease; and the inhibition of a transcription factor signal transducer and activator of transcription 3 (STAT3 inhibitor). Antisense oligonucleotides (ASOs) and RNA interference (RNAi) are the other therapeutic strategies for targeting transcription and translation of hepcidin [24] and minihepcidins (small active peptides)mimetics of iron-regulatory hormone hepcidin [25].…”
Section: Hepcidin and Ferritin-ferroportin Axismentioning
confidence: 99%